ESSENTIAL OILS OF THYMUS VULGARIS AND MELALEUCA ALTERNIFOLIA AS CONTROL AGENTS AGAINST KLEBSIELLA SPP.: AN IN VITRO DISK-DIFFUSION EVALUATION - Silva , Saulo Abreu Almeida da; Junior , José Geraldo de Vargas; Mendonça , Pedro Pierro; Pierro, Priscilla Cortizo Costas; Bolzan , Raphael Pires; Venancio, Aldino Neto; Santo, Mario Ferreira Conceição; Menini, Luciano (Revista Internacional de Ciências, 2026)
Aquaculture is the fastest-growing sector in various parts of the world. However, production intensification can lead to several issues, including microbial diseases. One of the most significant concerns in aquaculture production is Klebsiella spp., due to its high infectivity, rapid multiplication, and antibiotic resistance. Consequently, the search for alternatives to conventional treatments is essential. This study aimed to evaluate the effect of essential oils from Thymus vulgaris and Melaleuca alternifolia as alternative treatments against Klebsiella spp. in in vitro assays. The essential oil profiles were determined using gas chromatography with a flame ionization detector (GC-FID) and a mass spectrometry detector (GC-MS). The major compounds of Thymus vulgaris essential oil were carvacrol, thymol, and p-cymene. The predominant compounds in Melaleuca alternifolia essential oil were terpinen-4-ol, γ-terpinene, and α-terpinene. Both oils demonstrated antibacterial potential in controlling Klebsiella spp.; Thymus vulgaris essential oil performed better, achieving larger inhibition zones at lower concentrations. Five Klebsiella spp. Isolates from fish lesions were tested. Oxytetracycline (terramycin) was used as a positive control; p < 0.05 (Tukey’s test).